SOCIALIZATION OF PHASE C INDONESIAN STUDENT FITNESS TEST (TES KEBUGARAN SISWA INDONESIA / TKSI) - Ians Aprilo; Poppy Elisano Arfanda; M. Adam Mappompo; M. Said Zainuddin; Retno Farhana Nurulita (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Student's physical fitness is one of the important things in supporting the implementation of learning at school. This Community Service is an outreach activity about the Indonesian Student Fitness Test (TKSI), which is still something new, so many Physical Education, Sports, and Health (PJOK) teachers do not yet understand it. Apart from socializing about TKSI, another aim is to determine the fitness level of elementary school (SD) students in grades 5 and 6. The method used is to explain how TKSI is implemented and demonstrate its implementation. The result of this service is that the average student's fitness is in the good category.